Parenting Pembelajaran Berbasis Teknologi Bagi Ibu Dharma Wanita FASILKOM Universitas Jember - Irawati, Tri Novita; Mahmudah, Muhlisatul; Nugraheni, Dyah Ayu (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
This service activity aims to increase the understanding of Dharma Wanita FASILKOM Jember University members regarding technology-based parenting through interactive training. The method used is Participatory Action Research (PAR) which includes identification, planning, implementation and reflection stages. The material includes digital parenting, the use of educational applications such as ChatGPT, Kahoot, Quizizz, and SUNO AI, as well as preventing the negative impacts of using technology. The evaluation results showed an increase in participants' understanding, with 70% of questions answered correctly via Quizizz and 90% via Kahoot. Participants also showed high enthusiasm in discussions and simulations, reflecting the program's success in building adaptive parenting capacity.